Capsaicinoids as Green Corrosion Inhibitors: Quantum Chemical and Monte Carlo Simulation Studies - Junaidi, E.; Purwoko, A.A.; Hadisaputra, S.; Iskandar, Z.; Hamdiani, S. (Asian Journal of Chemistry, 2021)
The corrosion inhibition test of capsaicinoids extract from peppers has been previously reported using gravimetric and electrochemical analysis. Results showed that capsaicinoids have good potential as corrosion inhibitors because of their high corrosion inhibition efficiency. However, it should be noted that several types of capsaicinoids are present in the capsaicinoids extract. This variation causes previous study to be unable to identify the compounds with the most potential as corrosion inhibition. In present study, the density functional theory (DFT), ab initio and Monte Carlo simulation studies explain the problem. The quantum parameters of the four major compounds in capsaicinoids such as capsaicin, dihydrocapsaicin, nordihydrocapsaicin and homocapsaicin were compared to predict the compound with the highest corrosion inhibition. The Monte Carlo simulation study was applied to study the interaction mechanism between capsaicinoids and metal surfaces. The quantum parameter has linearity with the adsorption energy of capsaicinoids on the metal surface. The most significant role in inhibiting corrosion was shown by homocapsaicin, followed by capsaicin, dihydrocapsaicin and norcapsaicin. The theoretical study is expected to bridge the gap in an experimental study in designing an effective corrosion inhibitor.